Kebijakan Peningkatan Kualitas Pelayanan Terpadu Satu Pintu (PTSP) di Kantor Kementerian Agama Kabupaten Purbalingga - Erlinda (JURNAL ILMIAH GEMA PERENCANA, 2025)
This Policy Paper describes the One-Stop Integrated Service (PTSP) at the Purbalingga Regency Ministry of Religious Affairs Office as a bureaucratic reform strategy to improve the efficiency, transparency, and accountability of public services. This study aims to identify efforts to optimize the quality of PTSP services by analyzing policies, processes, and supporting and inhibiting factors. This paper uses a qualitative method with a descriptive analysis approach, where data is obtained through document studies, interviews, and observations. The results of the study indicate that the implementation of PTSP has had a positive impact on service time, reduced bureaucratic procedures, and increased public satisfaction. However, several challenges remain, such as limited competent human resources, inadequate technological infrastructure, and lack of public understanding of service procedures. The optimization efforts identified include strengthening human resource capacity through ongoing training, modernizing information technology systems to facilitate access to services, and increasing socialization in the community. In addition, collaboration with external parties, such as educational institutions and religious organizations, is also a key strategy to support the success of this policy. The policy recommendations provided include allocating an adequate budget for the development of PTSP, simplifying regulations that hinder service efficiency, and implementing an evaluation system based on key performance indicators (IKU) to ensure the sustainability of quality improvements.